Vegetation and climate change during the Medieval Climate Anomaly and the Little Ice Age on the southern Cape coast of South Africa: Pollen evidence from Bo Langvlei. (December 2020) - du Plessis, Nadia; Chase, Brian M; Quick, Lynne J; Haberzettl, Torsten; Kasper, Thomas; Meadows, Michael E
This paper presents continuous, high resolution fossil pollen and microcharcoal records from Bo Langvlei, a lake in the Wilderness Embayment on South Africa's southern Cape coast. Spanning the past ~1300 years and encompassing the Medieval Climate Anomaly (MCA; c. AD 950–1250) and the Little Ice Age (LIA; c. AD 1300–1850), these records provide a rare southern African perspective on past temperature, moisture and vegetation change during these much debated periods of the recent geological past. Considered together with other records from the Wilderness Embayment, we conclude that conditions in the region during the MCA chronozone were – in the context of the last 1300 years – likely relatively dry (reduced levels of Afrotemperate forest pollen) and perhaps slightly cooler (increased percentages of Stoebe -type pollen) than present. The most significant phase of forest expansion, and more humid conditions, occurred during the transition between the MCA and the most prominent cooling phase of the LIA. The LIA is clearly identified at this locality as a period of cool, dry conditions between c. AD 1600 and 1850. The mechanisms driving the changes observed in the Bo Langvlei pollen record appear to be generally linked to changes in temperature, and changes in the influence of tropical circulation systems. During warmer periods, moisture availability was higher at Bo Langvlei, and rainfall was perhaps less seasonal. During colder periods, precipitation resulting from tropical disturbances was more restricted, resulting in drier conditions. While increased precipitation has been reported during the LIA from Verlorenvlei in the Western Cape as a result of an equatorward displacement of the westerly storm-track at this time, the opposing response at Bo Langvlei suggests that any increased influence of westerlies was insufficient to compensate for the concurrent reduction in tropical/local rainfall in the region.